3D modeling of pulsed thermal NDT: Back to basic features and subtle phenomena. (September 2022) - Vavilov, Vladimir P.
Abstract: By using advanced 3D modeling of thermal nondestructive testing (TNDT) problems, most of basic TNDT features are shortly described, but the emphasis is put on the analysis of some subtle physical phenomena which may be observed in TNDT experiments, and most of them have not been properly reflected in the earlier studies. These are: 1) the "smashing" of 2D defect surface "footprints" because of 3D heat diffusion, 2) practical approaches to determining defect lateral size by their surface temperature indications, 3) clarification of a limiting defect size/depth ratio providing reliable detection of subsurface defects; 4) inversion of "classical" temperature signals at longer times, 5) defect shading, 6) influence of composite anisotropy on defect detectability, and 7) combined heating/cooling allowing to govern behavior of surface temperature profiles. Highlights: Limiting defect size/depth ratio is to be précised depending on material and defects. Inversion of temperature signals can be used for discriminating defects from clutter. Recognition of deeper defects through the shallower ones is difficult. Combined heating/cooling allows to govern behavior of surface temperature profiles. Composite anisotropy does not much affect differential temperature signals.